Locating the Risk: Using Participatory Mapping to Contextualize Perceived HIV Risk across Geography and Social Networks among Men Who Have Sex with Men in the Deep South. Issue 7 (2nd September 2022) - Arnold, Trisha; Stopka, Thomas J.; Gomillia, Courtney E. S.; Murphy, Matthew; Johnson, Kendra; Chan, Philip A.; Klasko-Foster, Lynne; Rogers, Brooke; Soler, Jorge H.; Monger, Mauda L.; Jacque, Erin; Sutten Coats, Cassandra; et al.
ABSTRACT: HIV incidence among African American (AA) young men who have sex with men (YMSM) has remained stable even though they made up the largest number of new HIV diagnoses among men who have sex with men (MSM) in 2017. HIV spreads at increased rates in dense sexual networks. Identifying the location of risk behaviors "activity spaces" could inform geographically circumscribed HIV prevention interventions. Utilizing the modified social ecological model we completed five semi-structured focus groups incorporating a modified social mapping technique, based on Singer et al.'s approach. Participants included 27 AA YMSM. Focus groups explored how and where HIV transmission happens in Jackson, Mississippi. Result themes included: 1) location of sexual behaviors, 2) knowledge of geographic hotspots of HIV infection in Jackson, and 3) traveling to meet partners: at home and away. HIV transmission or "activity spaces" may be occurring outside identified HIV hot spots. Mixed geospatial and qualitative methods offered a comprehensive assessment of where HIV transmission occurs, and suggests that geographically circumscribed interventions may need to focus on where individuals living with HIV reside and in specific geographic locations where they engage in behaviors that raise their HIV acquisition risks.